Developmet of an E-Module for Pancasila Education Subject Based on the Pancasila Student Profile for Fourth-Grade Elementary School Students - Kadek Ayu Indraswari Ayu Indraswari; I Gusti Agung Ayu Wulandari (Mimbar Pendidikan Indonesia, 2025)
The limited variety of instructional media used by teachers in teaching Pancasila Education contributes to low student engagement and academic achievement. This limitation necessitates the development of innovative learning resources that align with character building and 21st-century competencies. This study aims to develop and evaluate the effectiveness of a Pancasila Student Profile-based e-module by implementing the Dick and Carey instructional design model. This research employed a research and development (R&D) design involving 30 fourth-grade students as trial subjects. Data were collected using multiple-choice objective tests, feasibility questionnaires, and observation sheets, while data analysis was conducted using both qualitative and quantitative approaches. The results indicate that the developed e-module met the feasibility criteria, with scores from content experts (95%), language experts (93.33%), media experts (98.33%), instructional design experts (94.44%), individual trials (91.66%), and small-group trials (92.77%), all categorized as “Excellent.” Effectiveness testing using a t-test produced a significance value of 0.001 (< 0.05), indicating a significant positive effect of the e-module on student learning outcomes. These findings suggest that the Pancasila Student Profile-based e-module can serve as an effective instructional medium to enhance students’ cognitive competencies as well as character development.